SOCIODEMOGRAPHIC CHARACTERISTICS AND MIGRATORY PATH OF PORTUGUESE ENTREPRENEURS IN LONDON - Magalhães, Sara Moreira Coelho de (2016)
This study is part of a project that started in 2012, which addresses other European territories (Nice, Monaco and Andorra) and is funded by the Portuguese Foundation for Science and Technology. The goal is to examine, empirically– by using data collected from questionnaires conducted, in 2013 and 2014, within a sample of Portuguese entrepreneurs in London – the main socio-demographic characteristics of the Portuguese migrant entrepreneurs and their migration paths. From the results of this study, it can be concluded that the professional career path of these entrepreneurs in Portugal, and afterwards in London, was mainly in the "˜accommodation and food services' sector, showing that there is a continuation in terms of professional experience and investment in this regard. The originality of this workÂ is the study of the ethnic and economic emigration of Portuguese in London, which, until now, it was not enough researched and analysed. Given the increasing number and importance of entrepreneurs in this community, a more comprehensive knowledge of migrant entrepreneurship can help in promoting policies that encourage and sustain immigrant entrepreneurship in this country. Then, more specific data about Portuguese immigrant entrepreneurship are needed.